One-step hexaplex immunoassays by on-line paper substrate-based electrospray ionization mass spectrometry for combined cancer biomarker screening. Issue 13 (26th February 2021) - Xu, Shuting; Liu, Mingxia; Feng, Jie; Yan, Guangtao; Bai, Yu; Liu, Huwei
Abstract : On-line paper substrate based electrospray ionization mass spectrometry for hexaplex immunoassays. Abstract : Mass spectrometry (MS) is attractive as a multiplexed immunoassay readout benefiting from its high sensitivity, speed and mass resolution. Here, a simple paper-based hexaplex immunoassay with an on-line MS readout was proposed, using functionalized paper as the immune substrates, along with rhodamine-based mass tags assembled on gold nanoparticles prepared as the mass probes (MPs). Simultaneous immune capture and labeling were conducted in one step on paper substrates in 96-well plates with a high throughput within 30 minutes, and the on-line efficient dissociation of the mass tags highly facilitated the hexaplex readout of the immune signals by a newly established on-line paper substrate-based electrospray ionization-MS setup. Six MPs were synthesized for the simultaneous quantification of six important cancer protein markers (cancer antigen 15-3, cancer antigen 19-9, carcinoma embryonic antigen, cancer antigen 125, human epididymis protein 4, and alpha fetoprotein) using only 10 μL serum, presenting satisfactory sensitivity, accuracy and specificity. This platform was further tested in screening for the six biomarkers in serum samples of patients with breast, liver and gastric cancers, showing its high potential for sensitive and specific early cancer diagnosis.